Spectrum of breast asymmetries: a pictorial essay - Hassan, Radhiana; Samad Cheung, Humairah; Abdul Rashid, Mohd Amran; Che Mohamed, Siti Kamariah (2009)
Introduction: Asymmetric breast tissue is a relatively common mammographic finding and is usually benign. It might be due to a normal variation, postoperative changes or hormone replacement therapy. However, an asymmetric area may indicate a developing mass or an underlying cancer.